Sob suspeita: juventudes negras estigmatizadas à mira da violência policial - Costa, Ana Clara Gomes (2017)
Based on a proposal that sees communication beyond the media processes, this research investigates how communicative actions present in everyday life corroborate to strengthen discourses, ideologies and power relations, marginalizing, segregating and stigmatizing blacks youths, once that it is not recognized by society as a social group formed by subjects of rights. The racism over blackness and the black body establishes the stereotype of the black person’s suspicion and attachment to banditry. This reality conceives a trajectory of violence, violations and inconsistencies with the black population, which is blamed for the high crime rates that increase the statistics of urban violence in the city of Goiânia. On the basis of racism and socioracial hierarchization, blacks youths are subjugated and embedded in a chain of extirpation of formal rights. They are also subject to violent actions by the society and the police, which has it as the main target of investigations and preventive actions. The police violence is, therefore, legitimated by society as a way of containing urban violence. This, in turn, is represented by the association of the blacks youths to the crimes occurred in the spaces of the city. In addition to the communicative processes of everyday life that contribute to the legitimacy of police violence, media communication also ratifies racism and exclusion processes, since a discourse of effectiveness and efficiency is used in the face of police actions that fight crime, under the constant vigilance and punishment of blacks youth. With the use of the methodological procedures of the focus group, linked to observation, reporting and documentary analysis, this research aims to analyze how black bodies are instrumented by communicative actions to legitimize police violence against the black youth. The reaffirmation of such bodies and the recognition that it is essential to combat racism stemming from the stigmatization of black bodies can be a strong point in the fight against racism.